An anthraquinone–enzyme–peptide hybrid as a photo-switchable enzyme. Issue 75 (3rd September 2018) - Sotokawa, Shota; Kitamura, Takashi; Takahashi, Daisuke; Toshima, Kazunobu
Abstract : The purpose-designed anthraquinone–horseradish peroxidase–cell penetrating peptide hybrid1 exhibited cell permeability and enzymatic activity without photo-irradiation whereas significant self-degradation and loss of enzymatic activity occurred upon photo-irradiation in living cells. Abstract : A purpose-designed anthraquinone–horseradish peroxidase (HRP)–cell penetrating peptide hybrid1 showed high and effective cell permeability. Furthermore, 1 exhibited enzymatic activity without photo-irradiation, whereas significant self-degradation and loss of enzymatic activity occurred upon photo-irradiation in living cells.